Strategi Komunikasi Pemasaran Pada Guest House Gintribu Dolat Rakyat dalam Meningkatkan Pengunjung - Arya Dwi Putra; Rasyid, Abdul (Universitas Muhammadiyah Sorong, 2024)
Business developments in the field of accommodation services are currently increasing. Lodging services are developing rapidly so that they can create competition between tourist attractions in attracting tourists. The rapid changes in the business environment force tourist attractions to continue to develop existing tourist locations and look for new ways to market them. Therefore, researchers conducted research on businesses in the lodging services sector. Gintribu Dolat Rakyat Guest House is the place of choice for researchers to research the marketing strategies used by business owners at this guest house. The marketing communication strategy used by Guest House GINTRIBU Dolat Rakyat uses the Theory of Segmentation, Targeting and Positioning (STP), first developed by Wendell R. Smith. Researchers apply qualitative methods by conducting observations, interviews and descriptive document analysis. This research aims to explore the marketing communication strategies carried out by Gintribu Dolat Rakyat Guest House in marketing and increasing visitors. As well as giving hope to turn the strategy implemented by this guest house into a study in opening up business opportunities in the field of lodging services.